The Impact of a Spiritual Well-Being program on Preventing Quarter Life Crisis in Association Muhammadiyah Thailand Students - Wantini, Wantini; Perawironegoro, Djamaluddin; Hopid, Abdul; Sama-Alee, Abdunrorma (FKIP Universitas Lampung, 2025)
The Impact of a Spiritual Well-Being program on Preventing Quarter Life Crisis in Association Muhammadiyah Thailand Students. Objective: This program aims to provide preventive action in the form of spiritual well-being training to prevent Quarter Life Crisis among students in the Muhammadiyah Association of Thailand. Method: The quantitative research method approach with an experimental design of one group pretest and posttest design. This study was attended by 41 students of the Muhammadiyah Association of Thailand from the Faculty of Education, Fatoni University, Thailand. The sample was selected using the purposive sampling technique. Findings: The results of the independent sample t-test analysis showed a t-value of -5.583 with a degree of freedom (df) of 40, indicating a very significant difference between the pre-test and post-test results. The significance value (2-tailed) of 0.000 is less than 0.05 after the implementation of this training. This shows that the program is effective in reducing the level of quarter-life crisis in Thai Muslim students. This finding supports the theory that spiritual well-being helps individuals face life crises more meaningfully. This program strengthens the meaning of life, self-reflection, and Islamic values, which have been shown to increase resilience and inner peace. Conclusion: This program offers substantial advantages, including the enhancement of students' inner well-being, the reduction of tension, and the assistance in identifying the purpose of life and making informed decisions during the transition to early adulthood. These results have the potential to serve as a preventative measure for the quarter-life crisis. The implications encompass the enhancement of mental resilience, social relationships, and spirituality in the field of education. Despite the presence of challenges such as time constraints and disparities in comprehension, partner support is extremely beneficial. The outcomes of this training are incorporated into the learning process and will be implemented as a consistent program in order to provide students with the support they need to confront life's obstacles from a spiritual perspective. Keywords: spiritual training, well-being, quarter life crisis, the muhammadiyah association of Thailand.